2015
DOI: 10.1016/j.bej.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamethoxazole and isoproturon degradation and detoxification by a laccase-mediator system: Influence of treatment conditions and mechanistic aspects

Abstract: a b s t r a c tThe potential of laccase-mediator systems (LMS) for the removal and detoxification of two wastewater micropollutants, the antibiotic sulfamethoxazole (SMX) and the herbicide isoproturon (IPN), was assessed. The influence of various parameters on micropollutant oxidation rates, such as pH, mediator, enzyme and pollutant concentrations, was investigated with three mediators: 2,2 -azinobis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS), syringaldehyde (SA) and acetosyringone (AS). Both pollutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 39 publications
4
60
1
Order By: Relevance
“…Laccases (EC 1.10.3.2) are a promising group of oxidoreductases that have high activity in oxidizing phenolic compounds and arylamine, including phenols, polyphenols, methoxy‐substituted phenols, aromatic and aliphatic amines, by using molecular oxygen as the electron acceptor without the need for cofactors (Strong & Claus, ; Thakur, Patel, Gupte, & Gupte, ). Prior studies have demonstrated the use of laccases for effective degradation of emerging contaminants, such as endocrine disruptors (bisphenol A [Zdarta, Antecka et al, ] and triclosan [Le et al, ]), pharmaceuticals (sulfamethoxazole [Margot, Copin, von Gunten, Barry, & Holliger, ] and naproxen [Tran, Urase, & Kusakabe, ]), and pesticides (bromofenoxim [Torres‐Duarte, Roman, Tinoco, & Vazquez‐Duhalt, ] and carbofuran [Wang, Liu, Yao, Zhang, & Bao, ]). However, using free enzymes faces challenges including short enzyme lifetimes, time‐consuming and expensive purification processes, and nonreusability (Sheldon & van Pelt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Laccases (EC 1.10.3.2) are a promising group of oxidoreductases that have high activity in oxidizing phenolic compounds and arylamine, including phenols, polyphenols, methoxy‐substituted phenols, aromatic and aliphatic amines, by using molecular oxygen as the electron acceptor without the need for cofactors (Strong & Claus, ; Thakur, Patel, Gupte, & Gupte, ). Prior studies have demonstrated the use of laccases for effective degradation of emerging contaminants, such as endocrine disruptors (bisphenol A [Zdarta, Antecka et al, ] and triclosan [Le et al, ]), pharmaceuticals (sulfamethoxazole [Margot, Copin, von Gunten, Barry, & Holliger, ] and naproxen [Tran, Urase, & Kusakabe, ]), and pesticides (bromofenoxim [Torres‐Duarte, Roman, Tinoco, & Vazquez‐Duhalt, ] and carbofuran [Wang, Liu, Yao, Zhang, & Bao, ]). However, using free enzymes faces challenges including short enzyme lifetimes, time‐consuming and expensive purification processes, and nonreusability (Sheldon & van Pelt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Highly reactive phenoxyl radicals are produced due to oxidation of SA by laccase. These radical species can be consumed as they react with TrOCs (Margot et al, 2015). However, due to continuous addition of SA in excess, copious amount of reactive radical species are likely to be produced.…”
Section: Enzymatic Membrane Reactormentioning
confidence: 99%
“…Numbers within parenthesis indicates number of data points. Data was collected from the following studies:[82,83,84,85,103,104,105,106,107,108].…”
mentioning
confidence: 99%